Taxi booking system using mobile location based service - Chua, Khim Teck. (2009)
The high cost of vehicle ownership in Singapore has deterred a portion of people from getting their own private vehicles, thus in order to get around Singapore easily, the next best form of transportation is taxi. The popularity of taxi has grown in recent years, with the government’s recent initiatives to approve more taxi operator’s license. This creates a variety dispatch systems being used, each catering to their own taxi operators and not interlinked to each other and has caused a few problems to emerge and decreased the effectiveness of a good transportation in Singapore. This project will identify the problems with the current taxi infrastructure in Singapore and evaluate proposed solution to address the problems. The project aims to research and develop a new system of taxi booking and dispatch by using mobile phones. It also aims to unify the taxi booking systems in Singapore.